(untitled) (Світ фінансів, 2017)
Тиркало Р. І., Ткачук Н. М. Проблеми оцінки ринкової вартості власного капіталу банку. Розглянуто особливості витратного, порівняльного та доходного підходів ринкової оцінки вартості власного капіталу банку. Виявлено переваги та недоліки кожного з цих підходів, а також можливості їх використання вітчизняними банками. Обґрунтовано доцільність виділення балансової, економічної, ринкової та дійсної вартості власного банківського капіталу відповідно до використовуваних підходів оцінки його величини. Tyrkalo R., Tkachuk N. Problems of the market evaluation of the bank own assets. The peculiarities of the cost-based, comprehensive and earning approaches to the market evaluation of equity of bank capital has been considered. The advantage and disadvantages of each of these approaches, as well as opportunities of their usage by Ukrainian banks, are revealed. The expediency of the delineation of balance, economic, market and real value of equity of bank capital in accordance to the used approaches of the evaluation of its value is grounded.